CERTAIN PROBLEMS OF LEGAL SUPPORT OF THE AIR TRANSPORT INDUSTRY OF UKRAINE FROM THE STANDPOINT OF MODERNITY - Zhmur, Nataliia; Shpak, Inna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to determine the state of legal support of the air transport industry of Ukraine in the conditions of war, the main problems in this area, to provide scientific and practical recommendations for improving the legislative regulation of existing problems in Ukraine, taking into account European standards and the experience of European countries. Research methods: the work uses general methods of scientific cognition, determined by the purpose and objectives of this study, namely: logical generalization, analysis and synthesis, comparison and systematic approach, as well as comparative legal and systemic-structural methods. Results: the article highlights the current realities and problems of legislative regulation of the air transport industry of Ukraine in the modern conditions, and identifies scientific and practical recommendations for improving the relevant legislation at the current stage of development of the air transport industry, taking into account the European standards. Discussion: Ukrainian legislation in the field of civil aviation is undergoing reform. Today, a number of problematic aspects need to be addressed, including the procedure for investigating aviation accidents, flight safety, the introduction of new innovative technologies, determining the optimal areas for improving national legislation and bringing it as close as possible to European standards. A comprehensive solution to these problems and close supervision of this process will lead to the restoration and development of the aviation industry of Ukraine, taking into account the challenges of our time.